2008
DOI: 10.1016/j.ijrobp.2008.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Neuron Number Is Unchanged 1 Year After Fractionated Whole-Brain Irradiation at Middle Age

Abstract: Impairment on a hippocampal-dependent learning and memory test occurs 1 year after fractionated WBI at middle age. The same WBI regimen, however, does not lead to a loss of neurons or a reduction in the volume of hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 62 publications
(68 reference statements)
5
33
0
2
Order By: Relevance
“…Other studies have shown no reduction in the actual number or density of hippocampal neurons at 1 year after fractionated whole-brain irradiation, but alterations in the relative numbers of the N-methyl D-aspartate receptor subunits NR1, NR2A, and NR2B within the CA1 segment. Similar changes were not seen in the CA3 segment or dentate gyrus (12)(13). The long-term neurocognitive consequences of WBRT are well documented.…”
Section: Discussionmentioning
confidence: 63%
“…Other studies have shown no reduction in the actual number or density of hippocampal neurons at 1 year after fractionated whole-brain irradiation, but alterations in the relative numbers of the N-methyl D-aspartate receptor subunits NR1, NR2A, and NR2B within the CA1 segment. Similar changes were not seen in the CA3 segment or dentate gyrus (12)(13). The long-term neurocognitive consequences of WBRT are well documented.…”
Section: Discussionmentioning
confidence: 63%
“…To date, the disadvantage in the use of WBRT is determined by the risk of neurocognitive decline related to radiation and recently, several analyses showed that hippocampal-dependent functions are preferentially affected by radiotherapy [29,30]. Thus, to reduce this potential risk, some experiences evaluated hippocampal sparing during WBRT-SIB, using different arc therapies [14,17,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis showed that hippocampal-dependent functions, including learning, memory and spatial information processing, are preferentially affected by radiotherapy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus is a structure that is very sensitive to irradiation, and even relatively low-dose radiation exposures have been shown to cause a significant biphasic response in this area, which consists of an initial acute loss of SGZ cells mediated by the induction of apoptosis, followed by a delayed inflammatory response characterized by the loss of hippocampal neurons, reduced neurogenesis, microglial proliferation, and N-methyl-D-aspartic acid receptor remodeling (23,(27)(28)(29)(30)(31)(32)(33)(34)(53)(54)(55)(56). This damage may be irreparable (35).…”
Section: Discussionmentioning
confidence: 99%